2019
DOI: 10.3389/fphar.2019.01224
|View full text |Cite
|
Sign up to set email alerts
|

FGF10 Enhances Peripheral Nerve Regeneration via the Preactivation of the PI3K/Akt Signaling-Mediated Antioxidant Response

Abstract: The process of axonal regeneration after peripheral nerve injury (PNI) is slow and mostly incomplete. Previous studies have investigated the neuroprotective effects of fibroblast growth factor 10 (FGF10) against spinal cord injury and cerebral ischemia brain injury. However, the role of FGF10 in peripheral nerve regeneration remains unknown. In this study, we aimed to investigate the underlying therapeutic effects of FGF10 on nerve regeneration and functional recovery after PNI and to explore the associated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 62 publications
(67 reference statements)
1
44
0
Order By: Relevance
“…FGF10 is a member of the FGF family with multifunctional effect in the regulation of development, wound healing, and tissue regeneration. It has been proved that FGF10 can ameliorate cerebral I/R injury and spinal cord injury via inhibiting NF-kB-dependent inflammation and activating the PI3K/Akt signaling pathway (Li et al, 2016;Chen et al, 2017;Dong et al, 2019). In our previous study, we demonstrated that FGF10 can protect the kidney against apoptosis via the regulation of inflammatory response and autophagy (Tan et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…FGF10 is a member of the FGF family with multifunctional effect in the regulation of development, wound healing, and tissue regeneration. It has been proved that FGF10 can ameliorate cerebral I/R injury and spinal cord injury via inhibiting NF-kB-dependent inflammation and activating the PI3K/Akt signaling pathway (Li et al, 2016;Chen et al, 2017;Dong et al, 2019). In our previous study, we demonstrated that FGF10 can protect the kidney against apoptosis via the regulation of inflammatory response and autophagy (Tan et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, these therapeutic effects were partially abolished when AST was combined with LY294002. This result might be explained that the nerve tissue had the capability of synthetizing and secreting some antioxidant enzymes to resist SCII-induced oxidative damage, although this capability did not satisfied the demand of cellular antioxidant defense [38]. After administration of AST to the SCII rats, the PI3K/Akt/GSK-3β signaling pathway associated with antioxidant stress was activated, which further enhanced antioxidative capability and then promoted nerve regeneration.…”
Section: Discussionmentioning
confidence: 96%
“…Pik3r2 is a protein-coding gene that encodes the regulatory component of phosphoinositide 3-kinase (PI3K), which has a diverse range of cell functions including proliferation and survival. In peripheral nerve injury, the related PI3K/protein kinase B (Akt) pathway might be involved in the Schwann cell response to excessive oxidative stress-induced apoptosis [ 50 ]. Further validation regarding the pivotal role of the abovementioned regulating genes responsible for prolonged neuroinflammation is needed in the future.…”
Section: Discussionmentioning
confidence: 99%